A proposed model for the continued professionalisation of student affairs in Africa (Journal of Student Affairs in Africa, 2021)
This article presents a model that can inform the continued professionalisation of student affairs as both a field and a practice in Africa. After providing a brief overview of the African post-secondary educational climate and establishing student affairs as an internationally recognised profession, I analyse three pieces authored or co-authored by Mirko Noordegraaf (2003; 2007; 2011) that develop the concepts of socially constructed professionalism, management of practices-in-transition and hybrid professionalism. I then employ these concepts to create a professionalisation model that incorporates an awareness of the complex and diverse nature of African student affairs work. I next examine two key areas present across the modern African post secondary environment – career education and distance learning – and discuss how the model can guide student affairs professionalisation and practice when working in these important educational spaces. I conclude by briefly commenting on the potential for practitioners in the African context to develop new pathways forward for the international student affairs community.
Keywords: student affairs; career education; distance learning; professionalisation